A Survey on Blind Facial Image Enhancement Techniques - Sahithi, K; Karuna, G (International Journal of Computer Sciences and Engineering, 2025)
Image Enhancement is one of the challenging issue in image processing. The objective of enhancement is modifying an image by removing the noise for making it easier to identify the key features. The current proficient strategy for recuperating dependable nearby arrangements of thick correspondences between two pictures with some common substance. The technique is intended for sets of pictures delineating comparable districts procured by various cameras and lenses, under non-inflexible changes, under various lighting, and over various foundations. Here use of another coarse-to-fine plan in which nearest-neighbor field calculations utilizing Generalized Patch Match are interleaved with fitting a worldwide non-direct parametric shading model and amassing reliable coordinating districts utilizing locally versatile imperatives. Contrasted with past correspondence approaches, technique joins the better of two universes: It is thick, as optical stream and stereo reproduction strategies, and it is likewise powerful to geometric and photometric varieties, sparse feature matching. This shows the convenience of technique utilizing three applications for programmed case based photo improvement: altering the tonal attributes of a source picture to coordinate a reference, exchanging a known mask to a new image, and kernel, and portion estimation for picture deblurring. The present work investigated various image enhancement techniques for noise elimination and to identify the key features of the image.